THE ROLE OF PAYMENT AND PAYMENT FLOWS IN DETERMINING THE NATURE OF THE PAYMENT CIRCUIT - Sayfiddinov Ilhom Fayziddinovich (American Journals, 2025)
This scientific article discusses the scientific and practical aspects of the nature of payment circulation, the problems related to it and ways to solve them. It is clearly stated that determining the nature of the payment circulation requires determining the nature of the payment, and the possibility of determining the nature of the "payment circulation" without determining the nature of the "payment".
Keywords: Payment, payment turnover, insolvency, payment discipline, macroeconomic stability, monetization coefficient, GDP (Gross Domestic Product), money supply, money aggregate (M2), cash flow, investment, commercial bank, loan interest, accounts receivable, accounts payable.